Catechol-O-Methyltransferase Val158Met Polymorphism Is Associated with Anxiety, Depression, and Widespread Pressure Pain Sensitivity in Women with Chronic, but Not Episodic, Migraine. Issue 7 (27th November 2018) - Fernández-de-las-Peñas, César; Ambite-Quesada, Silvia; Florencio, Lidiane L; Palacios-Ceña, María; Ordás-Bandera, Carlos; Arendt-Nielsen, Lars
Abstract : This study found that the Val158Met rs4680 polymorphism does not appear to be involved in predisposition to suffer from migraine in women. Women with chronic, but not episodic, migraine with the Met/Met genotype showed higher levels of anxiety, depression and widespread pressure pain sensitivity. The Val158Met rs4680 polymorphism may be involved in the phenotypic expression of chronic migraine. Abstract: Objectives: To analyze the association between the rs4680 catechol-O-methyltransferase Val158Met polymorphism and to determine the association of this polymorphism with clinical, psychological, and pain sensitivity variables in women with episodic or chronic migraine. Methods: Fifty women with episodic migraine, 50 with chronic migraine, and 50 matched healthy women participated. After amplifying the Val158Met polymorphism by polymerase chain reaction, we assessed genotype frequencies and allele distributions. Participants were classified according to the Val158Met polymorphism genotype into Val/Val, Val/Met, or Met/Met. A headache diary was used for collecting migraine pain features. Disability was assessed with the Migraine Disability Assessment Scale, trait/state anxiety levels with the State-Trait Anxiety Inventory, and depression/anxiety with the Hospital Anxiety and Depression Scale. Pressure pain thresholds (PPTs) were bilaterally assessed over the temporalis, the upper trapezius, the second metacarpal, and the tibialis anterior. Results: The distribution of the rs4680 Val158Met genotype was not significantly different between women with and without migraine ( P  = 0.157). No differences in migraine features were found to be dependent on the Val158Met genotype. Women with the Met/Met genotype showed higher migraine-related disability than those with the Val/Val or Val/Met genotype in both migraine groups ( P  < 0.01). Women with chronic, but not episodic, migraine with the Met/Met genotype exhibited higher depressive and anxiety levels and lower PPTs than those with the Val/Val or Val/Met genotype. Conclusions: The Val158Met rs4680 polymorphism does not appear to be involved in predisposition to suffer from migraine; however, this genetic factor may be involved in the phenotypic expression of chronic migraine, as anxiety, depression, and widespread pressure pain sensitivity were greater in those women with chronic, but not episodic, migraine with the Met/Met genotype.